2022
DOI: 10.1136/bmjophth-2021-000830
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy versus Xen gel implant for the treatment of open-angle glaucoma: a 3-year retrospective analysis

Abstract: ObjectiveTo compare the two surgical techniques in terms of efficacy, safety, and postoperative management over 36 months of follow-up.MethodsThis retrospective clinical cohort study compared the outcome of trabeculectomy surgery and Xen gel implant in patients having uncontrolled glaucoma. Patients were recruited using the following inclusion criteria: uncontrolled intraocular pressure (IOP) on maximally tolerated medical therapy, healthy conjunctiva freely mobile in the superior sector, open-angle, glaucomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
14
1
2
Order By: Relevance
“…In a 24-month retrospective study, patients in the Xen 45 group experienced a significantly lower incidence of wound leak (0% vs. 15.8%), bleb leak (0% vs. 6%), and hypotony (1.8% vs. 10.5%) compared to trabeculectomy [ 17 ], and a retrospective study comparing trabeculectomy with Xen implant, both in combination with phacoemulsification, reported a higher incidence of hypotony after trabeculectomy (7.7% vs. 0%) [ 33 ]. In two retrospective Xen vs. trabeculectomy studies, the incidence of hypotony was not reported; however, the anterior chamber flattening, a condition commonly related to hypotony, was greatly more frequent in the trabeculectomy compared to the Xen group (19.6% vs. 1.5% and 14.7% vs. 0%, trabeculectomy vs. Xen, respectively) [ 34 , 35 ]. In one study, no late hypotony and hypotony maculopathy occurred after the first month of follow-up [ 36 ], and one study reported a similar incidence of choroidal folds and hypotony maculopathy in the two groups (hypotony maculopathy 1.1% Xen, trabe 0.6%) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 24-month retrospective study, patients in the Xen 45 group experienced a significantly lower incidence of wound leak (0% vs. 15.8%), bleb leak (0% vs. 6%), and hypotony (1.8% vs. 10.5%) compared to trabeculectomy [ 17 ], and a retrospective study comparing trabeculectomy with Xen implant, both in combination with phacoemulsification, reported a higher incidence of hypotony after trabeculectomy (7.7% vs. 0%) [ 33 ]. In two retrospective Xen vs. trabeculectomy studies, the incidence of hypotony was not reported; however, the anterior chamber flattening, a condition commonly related to hypotony, was greatly more frequent in the trabeculectomy compared to the Xen group (19.6% vs. 1.5% and 14.7% vs. 0%, trabeculectomy vs. Xen, respectively) [ 34 , 35 ]. In one study, no late hypotony and hypotony maculopathy occurred after the first month of follow-up [ 36 ], and one study reported a similar incidence of choroidal folds and hypotony maculopathy in the two groups (hypotony maculopathy 1.1% Xen, trabe 0.6%) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its efficacy in treating normal-tension glaucoma (NTG) and achieving low intraocular pressure in patients with advanced glaucoma, the use of trabeculectomy is important and will likely persist. Trabeculectomy also offers better IOP lowering compared to the Xen 45 Gel stent [61].…”
Section: Trabeculectomymentioning
confidence: 99%
“…[22][23][24] In addition, the information about the long-term effect of XEN45 device is limited, with only few papers evaluating its effectiveness beyond 24 months. 17,[25][26][27][28][29] Moreover, the question of whether there are any differences in IOP lowering or reduction of ocular hypotensive medications between XEN alone or in combination with phacoemulsification in the long-term remain.…”
Section: Introductionmentioning
confidence: 99%